Police officer competence in handling Alzheimer's cases: The roles of AD knowledge, beliefs, and exposure. (February 2019) - Sun, Fei; Gao, Xiang; Brown, Hillary; Winfree, L Thomas
This study seeks to understand the level of police officer competence for providing assistance during interactions with patients of Alzheimer's disease (AD), and to reveal the roles their knowledge of AD, beliefs of AD, and previous exposure to patients with AD play in influencing these competence levels. Data were collected from police officers in two Phoenix metropolitan-area police departments through focus group discussions and survey. Four focus groups comprised of 27 police officers discussed their perceptions of AD and challenges of dealing with individuals with AD. Building on the findings from the focus groups, an online survey ( n = 228) examined police officer AD knowledge, as well as their experience and competence in the handling of AD cases. Police participants had fair knowledge of AD with an average 71.8% accuracy rate. More AD knowledge ( B = 0.29) and higher levels of education ( B = 0.85) were associated with higher levels of competence of recognizing AD-related behaviors. Low levels of discomfort interacting with AD patients ( B = −0.75) and having a family member of dementia ( B = 1.32) were related to higher levels of competence of reacting appropriately to an AD patient. The findings suggest that information about the best practices for dealing with community residents with AD needs to be made available to police officers. To ensure a dementia-friendly environment, aging service providers need to reach out to local law enforcement departments and provide training that promotes AD knowledge, decreases AD-related stigma, and increases competence of handing dementia cases in a way that fits the policing culture.